A Note on Pasinetti's "Ricardian System" - Eygelshoven, P. J.; Kuipers, S. K. (Review of Economic Studies, 1981)
Journal Article A Note on Pasinetti's “Ricardian System” Get access P. J. Eygelshoven, P. J. Eygelshoven University of Groningen Search for other works by this author on: Oxford Academic Google Scholar S. K. Kuipers S. K. Kuipers University of Groningen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 1, January 1981, Pages 185–186, https://doi.org/10.2307/2297132 Published: 01 January 1981 Article history Received: 01 October 1979 Accepted: 01 May 1980 Published: 01 January 1981